Perbandingan kematian nyamuk Aedes Aegypti pada penyemprotan Aerosystem menggunakan Bifenthrin dengan sistem Thermal Fogging menggunakan Malathion - Boesri, Hasan; Tri Boewono, Damar (Jurnal Kedokteran YARSI, 2008)
A small scale trial of Bifenthrin dosage 0,5 ml /m3 against DHF vector Ae. aegypti was conducted in the morning using Aerosystem in residential of Grobogan municipality in 2000. The air Bioassay test for insecticides tested showed that spraying at a distance of 0-5 meters caused 100% mortality of Ae. aegypti, after 24 hours of the treatment in the laboratory.